Facilitators and barriers of herbal medicine use in diabetic patients: A qualitative study - Ali Akbar Vaezi; Ahmad Sotoudeh; Nasim Namiranian; Mojtaba Fattahi Ardakani; Moradali Zareipour (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: In several countries such as Iran, the use of complementary and alternative medical products like herbal medicine is growing. There is, however, a lack of research on the prospects of herbal medicine patrons regarding facilitators and herbal medicine use barriers. The aim of this study was to explain the facilitators and the barriers of herbal medicine use in type 2 diabetes mellitus (T2DM) patients. MATERIALS AND METHODS: Qualitative one-to-one in-depth interviews were conducted with patients with T2DM from the Yazd Diabetes Research Center, using a semi-structured guide. For the recruitment of T2DM participants who used herbal medicine beside conventional medicine, purposeful sampling was used. Analysis of the data was carried out using the steps proposed by Graneheim and Landman strategies. RESULTS: Sixteen patients were interviewed. There were 2 subjects (facilitators and barriers herbal medicine use), 8 categories, and 89 initial codes. The facilitators included individual preferences, preparation skills, and family support and the factors obstructing the use of herbal medicine included insufficient skills about preparing, lack of easy access to consumption, insufficient of efficacy of herbal medicine, and negative properties of herbal medicine and taking time in preparing herbal medicine. CONCLUSION: Although some people use herbal medicine, the interest in use of herbal medicine is limited because of inadequate awareness of the impact and usage them. Therefore, the use of effective strategy in the integration of herbal remedies with conventional medicine can promote well-being of patients.